Some aspects of the activity of the eparchial orphanage ”Bishop Dionisie" in the city of Ismail (Confluenţe Bibliologice, 2024)
The study examines aspects of the activity of the Eparchial Orphanage ,,Bishop Dionisie” in the city of Ismail. Founded in 1934 under the guidance of Bishop Dionisie Erhan, this orphanage represents a signiﬁcant achievement in the history of the Diocese of Cetatea Albă-Ismail, reﬂecting care and compassion for orphaned children. The article highlights the eﬀorts undertaken to establish and sustain the orphanage, involving the local community and authorities. The moral-religious education of the orphans is entrusted to nuns, and the orphanage’s activities receive ﬁnancial and material support from believers and institutions. Over time, the orphanage expands, addressing the growing needs of the community. Despite his age, Bishop Dionisie Erhan remains actively involved in the institution’s management and initiates projects to enhance and expand its facilities. Thus, the Eparchial Orphanage becomes a remarkable work of social assistance and Christian education under the energetic and blessed guidance of Bishop Dionisie Erhan.
Keywords: social assistance; Christian education